“The Lecturer is Like a Housemaid”: the Position of Women Revealed by Female Metaphor Vehicles in Chinese - Hongying, Li (Sinología hispánica. China Studies Review, 2024)
Previous studies have shown that many metaphors conceptualize “women” in a derogatory way to present negative opinions about them. However, the issue of how “women” being metaphor vehicles function in discourse has rarely been addressed. This paper applies a discourse dynamics approach to conduct a multidimensional analysis of the linguistic, cognitive, affective, and socio-cultural-historical contexts of the 25 female metaphor vehicles identified in the modern Chinese novel Wei Cheng. The aim is to shed light on how this type of metaphors reflect the ideas, attitudes, and values towards women in Chinese discourse. The results show that, through highlighting certain negative features of their topics (i.e., male characters, female characters, university faculty and other non-human objects), these female metaphor vehicles at the same time display a corresponding view on women. Crucially, considering the historical background of the novel and the high degree of lexicalization of some of these metaphors in Chinese, these metaphor vehicles present a sexist view of women in traditional Chinese society and contribute to reinforce female gender stereotypes.